Determinants, effects and costs of domestic violence (2005)
This paper analyzes the determinants, effects and costs of domestic violence (DV) against women and children in Colombia. The most relevant factors that explain the occurrence of DV in a household are suffering from DV as a child and living with someone that frequently and excessively consumes alcohol. DV against women increases their probability of unemployment by 6.4 percentage points, lowers their earnings by approximately 40% and worsens their health. DV against children negatively affects their health, school attendance and academic attainment. It is estimated that at least 4.2% of Colombian GDP is lost due to indirect costs of DV.